Investigation of wire electrical discharge machining modes influences on crack formation and surface layer morphology of the Ti-6Al-2.5Mo-2Cr-0.3Si titanium alloy - A. A. Fedorov; D. A. Polonyankin; A. I. Blesman; N. V. Bobkov; A. V. Linovsky; Iu. O. Bredgauer; Yu. E. Zhdanova (Омский научный вестник)
The paper presents the results of the investigation devoted to the influence of wire electrical discharge machining modes on crack formation and surface layer morphology of the titanium alloy. The aim of the paper is to obtain interrelation data about processing modes with depth of microcracks penetration, as well as on the influence of processing modes on the morphology of the surface layer, in particular, on the group of parameters Rk. It is shown by using scanning electron microscopy that the depth of microcracks depends of the number of passes and processing conditions. The maximum depth is 12 μm after the first pass, the minimum is 0,9 μm after the fourth pass. The groups of parameters Rk study by the method of profilometry made it possible to conclude that the most favorable oil-retaining microrelief is formed after the third pass.